MATHEMATICAL INPUT

Q.1-5: In each of the following question, two rows of numbers are given. The resultant number in each row is to be worked out separately based on the following rules and the question below the rows of numbers are to be answered. The operation of numbers progress from left to right Rules : (i) If an odd number is followed by another composite odd number, they are to be multiplied, (ii) If an even number is followed by an odd number, they are to be added. (iii) If an even number is followed by a number which is the perfect square, the even number is to be subtracted from the perfect square, (iv) If an odd number is followed by a prime odd number, the first number is to be divided by the second number, (v) If an odd number is followed by an even number, the second one is to be subtracted from the first one. Q. 1. 58 17 5 85 5 n If ‘n’ is the resultant of the first row what is the resultant of the second row ? (1) 255 (2) 32 (3) 49 (4) 34 (5) None of these Q. 2. 24 64 15 m 11 15 If m is the resultant of the first row, what is the resultant of the second row ? (1) 165 (2) 75 (3) 20 (4) 3 (5) None of these Q. 3. 7 21 3 d 7 33 If d is the resultant of the first row, what will be the resultant of the second row ? (1) 40 (2) 138 (3) 231 (4) 80 (5) None of these Q. 4. 73 34 13 32 p 15 If p is the resultant of the first row, what is the resultant of the second row ? (1) 713 (2) 50 (3) 20 (4) 525 (5) None of these Q.5. 14 5 9 24 w 88 if w is the resultant of the first row, what is the resultant of the second row? (1) 171 (2) 283 (3) 195 (4) 165 (5) None of these Q.6-10: In each of the following questions two rows of numbers are given. The resultant number in each row is to be worked out separately based on the following rules and the question below the rows of numbers is to be answered. The operations of numbers progress from left to right. Rules : (i) If a two digit even number is followed by another even number the first one is to be divided by the second one. (ii) If an even number is followed by a prime number, the two are to be multiplied, (iii) If an odd number is followed by another odd number the two are be added, (iv) If a three digit number is followed by a two digit number which is the perfect square, the second number is to be subtracted from the first number, (v) If a three digit number is followed by a two digit number which is not the perfect square, the first number is to be divided by thesecondnumber. Q. 6. 16 7 25 m 23 22 If 'm' is the resultant of the first row, what is the resultant of the second row ? (1) 132 (2) 88 (3) 122 (4) 78 (5) None of these Q. 7. 97 45 71 48 8 11 What is the sum of the resultants of the two rows ? (1) 68 (2) 19 (3) 147 (4) 64 (5) None of these Q. 8. 125 64 33 282 x 39 If 'x' is resultant of the first row, what is the resultant of the second row ? (1) 45 (2) 42 (3) 39 (4) 36 (5) None of these Q.9. 84 14 13 360 24 17 What is the difference between the resultant of the first row and the second row ? (1) 100 (2) 46 (3) 56 (4) 90 (5) None of these

7 81 x 27 19 If 'x' is the resultant of the first row, what is the resultant of the second row ? (1) 87 (2) 114 (3) 4 (4) 6 (5) None of these Q. 11-15: In each of the following questions two rows of numbers are given. The resultant number in each row is to be worked out separately based on the following rules and the questions below the rows of numbers are to be answered. The operations of numbers progress from left to right. Rules : (i) If a two digit odd number is followed by a two digit odd number they are to be added. (ii) If a two digit even number is followed by a two digit odd number which is the perfect square, the even number is to be subtracted from the odd number, (iii) If a three digit number is followed by a two digit number the first number is to be divided by the second number. (iv) If a prime number is followed by an even number the two are to be added. (v) If an even number is followed by another even number the two are to be multiplied. Q. 11. 2 3 1 5 1 2 X 2 4 4 9 If X is the resultant of the first row, what is the resultant of the second row ? (1) 24 (2) 25 (3) 28 (4) 22 (5) None of these Q. 12. 3 7 1 2 2 1 3 8 8 1 1 4 What is the difference between the resultants of the two rows ? (1) 23 (2) 32 (3) 13 (4) 18 (5) None of these Q. 13. 1 6 8 3 2 132 1 1 X2 If X is the resultant of first row, what is the resultant of the second row ? (1) 192 (2) 128 (3) 132 (4) 144 (5) None of these Q. 14. 345 2 3 X 4 5 1 7 8 1 If X is the resultant of the second row, what is the resultant of the first row ? (1) 285 (2) 33 (3) 135 (4) 34 (5) None of these Q. 15. 1 2 2 8 8 4 3 7 2 2 1 8 What is the sum of the resultants of the two rows ? (1) 77 (2) 87 (3) 84 (4) 72 (5) None of these Q. 16-20: In each of the following questions two rows of numbers are given. The resultant number in each row is to be worked out separately based on the following rules and the question below the rows is to be answered. The operations of numbers progress from left to right. Rules: (i) If an even number is followed by another even number they are to be added. (ii) If an even number is followed by a prime number, they are to be multiplied. (iii) If an odd number is followed by an even number, the even number is to be subtracted from the odd number. (iv) If an odd number is followed by another odd number, the first number is to be added to the square of the second number. (v) If an even number is followed by a composite odd number, the even number is to be divided by the odd number. Q. 16. I. 84 21 13 II. 15 11 44 What is half of the sum of the resultants of the two rows? (1) 116 (2) 132 (3) 232 (4) 236 (5) None of these Q. 17. I. 45 18 12 II. 22 14 9 What is the product of the resultants of the two rows ? (1) 75 (2) 48 (3) 45 (4) 64 (5) None of these Q. 18. I. 12 7 16 II. 79 28 15 What is the difference between the resultants of the second row and the first row? (1) 276 (2) 176 (3) 100 (4) 156 (5) None of these Q. 19. I. 36 13 39 II. 77 30 7 What will be the outcome if the resultant of the second row is divided by the resultant of the first row? (1) 12 (2) 16 (3) 8 (4) 6 (5) None of these Q. 20. I. 65 11 12 II. 15 3 11 What is the sum of the resultants of the two rows? (1) 366 (2) 66 (3) 264 (4) 462 (5) None of these

Q.10. 24

Q. 21-25: In each of the following questions two rows of numbers are given. The resultant of each row is to be worked out separately based on the following rules, and the question below the row of numbers is to be answered. The operations of numbers in each row progress from left to right. Rules: (i) If an odd number is followed by another odd number, they are to be multiplied. (ii) If an even number is followed by another even number, the first number is to be divided by the second even number. (iii) If an even number is followed by the perfect square of an odd number, the first number is to be subtracted from the second number. (iv) If an odd number is followed by an even number the two are to be added. (v) If an even number is followed by an odd number which is not a perfect square, the square of the odd number is to be added to the even number. Q. 21. 96 16 81 = x 11 15 18 = y What is the value of y - 2x? (1) 108 (2) 33 (3) 105 (4) 36 (5) None of these Q. 22. 28 49 13 = x 37 12 22 = y What will be the sum of the resultants of the two rows? (1) 108 (2) 244 (3) 102 (4) 344 (5) None of these Q. 23. 18 5 17 = x 64 8 11 = y What will be the value of x + y? (1) 189 (2) 129 (3) 69 (4) 169 (5) None of these Q. 24. 9 15 50 = x 12 25 24 = y What will be the value of x ÷ y? (1) 18 (2) 8 (3) 5 (4) 6 (5) None of these Q. 25. 56 14 9 36 12 7 What will be the difference between the resultants of the two rows? (1) 14 (2) 21 (3) 5 (4) 26 (5) None of these

1-5: R1 = Resultant of the first row

R 2 = Resultant of the second row
58 17 5 [Used rule (ii)] ⇒ 75 5 15 [Used rule (iv)] n = 15 Now, let us find 85 5 15 [Used rule (iv)] ⇒ 17 15 255 [Used rule (i)] = 255 2. 2; 24 64 15 [Used rule (iii)] ⇒ (64 - 24) 15 40 15 [Used rule (ii)] 55 m = 55 Now, let us find . 55 11 15 [Used rule (iv)] ⇒ 5 15 75 [Used rule (i)] = 75 3. 3; 7 21 3 [Used rule (i)] ⇒ 147 3 49 [Used rule (iv)] d = 49 Now, let us find . 49 7 33 [Used rule (iv)] ⇒ 7 33 231 [Used rule (i)] = 231 4. 4; 73 34 13 [Used rule (v)] ⇒ 39 13 3 [Used rule (iv)] p=3 Now, let us find . 32 3 15 [Used rule (ii)] ⇒ 35 15 525 [Used rule (i)] = 525 5. 5; 107 14 5 9 [Used rule (ii)] ⇒ 19 9 171 [Used rule (i)] w = 171 Now, let us find . 27 171 88 ⇒ 195 88 [Used rule (ii)] 107 [Used rule (v)] 6. 5; 5 16 7 25 112 25 [Used rule (ii)] 87 [Used rule (iv)] m = 87 Now, let us find . [Used rule (iii)] [Used rule (v)] [Used rule (iii)] [Used rule (v)] 87 23 22 ⇒ 110 22 5 97 45 71 142 71 2 =2 Now, let us find R 2 . 48 1. 1;

7. 1;

⇒ 6
66

8 11 = 66

11 [Used rule (i)] [Used rule (ii)]

Hence, the required sum = R1 + R 2 = 2 + 66 = 68 8. 2; 125 64 33 33 [Used rule (v)] [Used rule (iii)] . 39 39 [Used rule (v)] [Used rule (iii)] 13 13 = 78 Let us find R 2 . 360 [Used rule (i)] [Used rule (ii)]

⇒ 61
94 x = 94

Now, let us find 282 282 ⇒ 3 42 9. 2; 84 x 94 39 = 42 14 78

⇒ 6

⇒ 15
32

24 17 = 32

17 [Used rule (v)] [Used rule (iii)]

Now, the required difference = R1 − R2 = 78 - 32 = 46 10. 4; 24 7 81 168 81 87 x = 87 Now, let us find 87 27 ⇒ 114 19 6 =6 . 19 [Used rule (iii)] [Used rule (iv)] [Used rule (ii)] [Used rule (iv)]

⇒ ∴1 ) R2 (R1

11. 5; Let us find the value of X (R1 ) . 23 15 12 [Used rule (i)] ⇒ 38 12 456 [Used rule (v)] Now, let us find R 2 . 456 24 49 [Used rule (iii)] [Used rule (i)] ⇒ 19 49 68 = 68 12. 3; Let us find R1 and R 2 R1 = 37 12 21 = 49 21 [Used rule (iv)] = 70 [Used rule (i)] Now, R 2 = 38 81 14 = 43 14 [Used rule (iii)] = 57 [Used rule (iv)] Thus, the reqired difference = 70 - 57 = 13 13. 1; Let us find R1 . R1 = 16 8 32 = 128 32 [Used rule (v)] = 4 [Used rule (iii)] Now, R 2 = 132 11 42 = 12 16 [Used rule (iii)] = 192 [Used rule (v)] 14. 4; Let us find . R 2 = 45 17 81 = 62 81 [Used rule (i)]

= 19 [Used rule (ii)] Now, R1 = 345 23 19 = 15 19 [Used rule (iii)] = 34 [Used rule (i)] 15. 5; Here, R1 = 12 28 84 = 336 84 [Used rule (v)] = 4 [Used rule (iii)] Now, R 2 = 37 22 18 = 59 18 [Used rule (iv)] = 77 [Used rule (iv)] Now, the reqired sum = 4 + 77 = 81 16. 1; R1 = 84 21 13 = (84 ÷ 21) 13 [Use rule (v)] = 4 13 = 4 × 13 [Use rule (ii)] = 52 R2 = 15 11 44 = (15 + 112) 44 [Use rule (iv)] = 136 44 = 180 [Use rule (i)] Now the required value

R1 + R 2 52 + 180 = = 116 2 2 17. 5; R1 = 45 18 12 = 27 12 [Use rule (iii)] = 15 [Use rule (iii)] R2 = 22 14 9 = 36 9 [Use rule (i)] =4 [Use rule (v)] Now, the required value of R1 × R2 = 15 × 4 = 60 18. 2; R1 = 12 7 16 = 84 16 [Use rule (ii)] = 100 [Use rule (i)] R2 = 79 28 15 = 51 15 [Use rule (iii)] = 51 + 152 [Use rule (iv)] = 276 Hence the required difference = R2 - R1 = 276 - 100 = 176 19. 3; R1 = 36 13 39 = 468 39 [Use rule (ii)] = 12 [Use rule (v)] R2 = 77 30 7 = 47 7 [Use rule (iii)] = 96 [Use rule (iv)] Now the required value of R2 ÷ R1 = 8 20. 4; R1 = 65 11 12 = 186 12 [Use rule (iv)] = 198 [Use rule (i)] R2 = 15 3 11 = 24 11 [Use rule (iv)] = 264 [Use rule (ii)] Hence the required value of R1 + R2 = 198 + 264 = 462 21-25: Read the rules carefully before reading the explanations. 21. 2; 96 16 81 [Use rule (ii)] ⇒ 6 81 81 - 6 = 75 [Use rule (iii)] x = 75 Again, 11 15 18 165 18 [Use rule (i)] 183 [Use rule (iv)] y = 183 Now, y - 2x
=

∴ ⇒ 52 + 8

= 183 - 2 × 75 = 33 22. 4; 28 49 13 (49 - 28) 13 21 13 [Use rule (iii)] = 273 [Use rule (i)] x = 273 Again, 37 12 22 49 22 [Use rule (iv)] = 71 [Use rule (iv)] y = 71 Now x + y = 273 + 71 = 344 23. 5; 18 5 17 17 [Use rule (v)] 17 ⇒ 33 = 561 [Use rule (i)] x = 561 Again, 64 8 11 64 ÷ 8 11 [Use rule (ii)] 8 11 = 129 [Use rule (v)] y = 129 Now, x + y = 561 + 129 = 690 24. 3; 9 15 50 9 × 15 50 [Use rule (i)] 135 50 135 + 50 [Use rule (iv)] = 185 x = 185 Again, 12 25 24 (25 - 12) 24 [Use rule (iii)] 13 24 (13 + 24) [Use rule (iv)] = 37 y = 37 Now, x ÷ y = 185 ÷ 37 = 5 25. 5; 56 14 9 (56 ÷ 14) 9 [Use rule (ii)] 4 9 (9 - 4) = 5 [Use rule (iii)] x=5 Again, 36 12 7 (36 ÷ 12) 7 [Use rule (ii)] 3 7 [Use rule (i)] 3 × 7 = 21 y = 21

Sign up to vote on this title
UsefulNot useful